The use of dry needles in the masseter and temporal muscles for the treatment of myofascial pain: Case report (Research, Society and Development, 2021)
Dry needling has the main purpose of inactivating the myofascial trigger points present in the tense muscle bands, which are hypersensitive areas to palpation that have the stimulus of local pain and / or referred pain. The present study aims to report a case of the use of dry needling in myofascial pain syndrome. A female patient complained of temporomandibular disorder and myofascial pain syndrome, with the presence of trigger points in the masseter and / or temporalis muscles. Initially, an anamnesis of the RDC / TMD type was performed, followed by palpation of the respective muscles. The patient marked the intensity of the pain before and after the dry needling session, on a visual analog scale. To analyze the effect of dry needling, the data obtained were organized from the comparison of the results achieved with the techniques performed. It was found that dry needling was effective in treating the myofascial trigger point, considerably decreasing pain immediately after the session.